2021
DOI: 10.30802/aalas-cm-20-000032
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Finding in the Development of an LPS-Induced Model of Synovitis in Sheep

Abstract: Models of transient synovitis that can be controlled with antiinflammatory and analgesic drugs have been used to studypain amelioration. To this end, we aimed to determine the dose of intraarticularly administered E. coli LPS that inducedsigns of synovitis without systemic signs in clinically healthy male castrated sheep (n = 14). In phase 1, a single dose of LPS(0.5, 1.0, 1.5, or 2.0 ng in a total volume of 0.5 mL) was administered into the right stifle joint. In phase 2, a dose of LPS (1.0 or 2.0 μg) in 0.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that systemic administration of LPS can lead to a generalized hyperalgesia [8]. Various mechanisms including the release of pro-in ammatory cytokines and glial cell activation have been proposed to be responsible for the LPS-induced hyperalgesia [7,8]. TNF-α and IL-1β are two essential cytokines involved in the in ammatory response as well as neuropathic pain induction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that systemic administration of LPS can lead to a generalized hyperalgesia [8]. Various mechanisms including the release of pro-in ammatory cytokines and glial cell activation have been proposed to be responsible for the LPS-induced hyperalgesia [7,8]. TNF-α and IL-1β are two essential cytokines involved in the in ammatory response as well as neuropathic pain induction.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to mimic the clinical presentation of diseases such as pain, in animal models, is important to achieve reliable medical results [7]. Nowadays, bacterial lipopolysaccharide (LPS) is widely used worldwide for arrays of investigations such as modeling of diseases, in ammatory mechanism evaluation, psycho/neurologic and behavioral studies both in vivo and in vitro [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous literature, there are models of self-limiting synovitis, such as intra-articular lipopolysaccharide injection in horses 29 or sheep-these kinds of settings can be used in tests of analgesics. 30 In arthritis research, multiple different arthritis models in animals have been used, but a single definitive method to model OA does not exist. 31 In rats, spontaneous OA is rare apart from minor focal changes.…”
Section: Discussionmentioning
confidence: 99%